Pendidikan Akhlak Sosial: Penanaman Nilai-Nilai Ukhuwah Islam dalam Tinjauan Ashabiyah Ibnu Khaldun - Arman; Ikawa Rosyida; Syamsul Arifin (Civiliza Publishing, Indonesia., 2026)
This research aims to examine the cultivation of Islamic ukhuwah values in social moral education through the perspective of Ibn Khaldun's ashabiyah. The research uses a library research method with a qualitative-descriptive approach through the analysis of various relevant literature sources. The results of the study show that social moral education plays an important role in shaping the character of students who have care, tolerance, responsibility, and social solidarity. The values of ukhuwah Islamiyah, such as brotherhood, help, and unity, are in harmony with the concept of ashabiyah of Ibn Khaldun which emphasizes the importance of social solidarity in people's lives. The integration of these two concepts is relevant to answer the challenges of individualism and moral crises in the modern era. Its implementation can be done through the habit of mutual cooperation, deliberation, social activities, and the example of educators. Thus, social moral education based on ukhuwah Islamiyah and ashabiyah of Ibn Khaldun can be a means of forming a generation that has noble character, has social awareness, and is able to contribute to community life.